Evaluasi Sistem Pembelajaran Online di SMP Negeri 5 Kabupaten Takalar - Nurqadriani; Suriyati, Suriyati; Mustamir (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Muhammadiyah Sinjai, 2023)
This study aims to evaluate the online learning system at SMP NEGERI 5, Takalar Regency. This typeof research is evaluation reasearch using the CIPP model (Context, Input, Process, Product). Thisresearch was conducted at SMP NEGERI 5 Takalar Regency with research subjects being students ofSMP NEGERI 5 Takalar Regency. The instrument used in this research is a questionnaire. Data wereanalyzed using quantitative methods. The results showed that: evaluation results based on the contextaspect obtained evaluation results of 95% very good category, on the input aspect obtained evaluationresults of 91% very good category, on the process aspect obtained evaluation results of 93% very goodcategory and on the product aspect obtained evaluation results of 79% in the good category. This meansthat the online learning program at SMP Negeri 5 Takalar Regency can be continued.